On Kantian Obligatory Ends and Their Maxims of Actions - Fahmy, Melissa Seymour (Studia Kantiana, 2023)
In the Doctrine of Virtue, Kant introduces the concept of an end that is also a duty and explains that these obligatory ends prescribe maxims of actions rather than actions themselves. A common view in the literature is that these maxims of actions are promotional in nature. In this paper, I work from the logic of ends to defend the view that each obligatory end prescribes multiple maxims of actions: the familiar positive, promotional maxim of actions, but also a negative, non-diminishing maxim of actions, epistemic maxims of actions, and dispositional maxims of actions. The account of obligatory ends I present is consistent with what Kant writes in the Doctrine of Virtue, but also develops the concept in ways that Kant did not, at least not explicitly.